Effects of wall conduction on natural convection in a porous triangular enclosure - Öztop, Hakan Fehmi; Varol, Yasin; Pop, Ioan (Springer Wien, 2008)
Conjugate natural convection in a two-dimensional triangular enclosure filled with a porous medium is examined in this article. It is assumed that the solid vertical wall is of finite conductivity and that the temperature of the inclined wall is lower than that of the vertical wall, while the horizontal wall is adiabatic. A finite difference method is used to solve the governing equations of convection and conduction for different parameters as Rayleigh number, width of the vertical solid wall, aspect ratio of the enclosure and thermal conductivity ratio between solid and porous media. It is found that heat transfer increases with increasing Rayleigh number and aspect ratio of the triangle, decreasing wall thickness and with the increase of the wall conductivity.
Keywords: Heat-Transfer